The dual spaces of new ?m - sequence spaces and their matrix maps - Ercan, Sinan; Bektas, Cigdem A. (Amer Inst Physics, 2017)
In this paper, we compute alpha-, beta-and gamma-duals of the new BK-spaces l(infinity)(lambda(m)), c(lambda(m)) and c(lambda(m)). We also give some classes of matrix transformations from these spaces to l(infinity), c, c(0), f and f(0)
11th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 04-08, 2016 -- Univ La Rochelle, La Rochelle, FRANCE
Keywords: Convergent